اسلام میں جنگ کے اصول و اخلاقیات :سیرت طیبہﷺ کی روشنی میں: The Principles and Ethics of War in Islam: In the Light of the Prophet’s (PBUH) Teachings - Qadri, Hafiz Muhammd Ahmad; Hussain, Sajjad (Al-Irfan, 2025)
This research study provides a comprehensive analysis of Islamic military ethics and the principles of military leadership exemplified by Prophet Muhammad ﷺ, based on practical observations from his Seerah. Islam has confined war within moral and legal framework, rather than viewing it as a mere display of power. Prophet Muhammad ﷺ demonstrated leadership that was grounded in principles such as Shura (consultation), equality, justice, patience, a realistic assessment of enemy power, and defensive strategies. This study explores practical examples from the Prophet’s military campaigns (Battles of Badr, Uhud, and the Trench) and peace agreements (such as the Treaty of Hudaybiyyah), shedding light on the spiritual, moral, and practical insights of his leadership. Furthermore, the Islamic principles of war are compared with modern international law, including the Geneva Conventions and United Nations regulations, to highlight the superiority and relevance of Islamic principles. The study concludes that Islamic military ethics offer a comprehensive, human-centered framework that can benefit contemporary global society if introduced and applied on a wider scale.